A Stub-Girder System for High-Rise Buildings - Colaco, Joseph P. (Engineering Journal, 1972)
The current trend to "systems" design in building construction has necessitated a new interdependence between the owner, architect, structural engineer, mechanical and electrical engineer, and the contractor. This paper describes one of the new systems—the integration of the mechanical ducts into the structural steel floor beams of a high-rise building. This system is called a stub-girder system. A conventional system of framing a floor in a structural steel structure is shown in Fig. 1(a). The structural system consists of wide flange beams spaced between 7 ft-0 in, and 11 ft-0 in. apart. The floor slab consists of approximately 3.25 in. of lightweight concrete on a metal deck. Composite action between the steel beams and the concrete slab is generally achieved by the use of suitable shear connectors. The mechanical ducts, lights, and ceiling construction are generally placed under the beams. In some instances, penetrations are made in the beams and girders to accommodate the ducts. For a building having a span of 40 ft-0 in. between the core and the exterior columns, the distance between the top of the floor slab and the ceiling is approximately 4 ft-0 in. The stub-girder system is shown in Fig. 1(b). The system consists of a girder spaced approximately 30 ft-0 in. on centers and spanning between the core and an exterior column. This girder consists of a high-strength, wide flange beam with stub pieces shop-welded on the top flange. Floor beams are placed over the girder (between the stub pieces) at approximately 10 ft-0 in. on centers. The floor beams are designed for continuity and are spliced near the points of inflection. The system is completed by the placement of a lightweight concrete slab on metal deck spanning between the floor beams. Composite action is ensured by the provision of shear connectors. The girder is shored while the concrete reaches its design strength.